Calcium mobilization in HeLa cells induced by nitric oxide. Issue 2 (5th June 2013) - Huang, Yimei; Zheng, Liqin; Yang, Hongqin; Chen, Jiangxu; Wang, Yuhua; Li, Hui; Xie, Shusen
Summary Nitric oxide (NO) has been proposed to be involved in tumor growth and metastasis. However, the mechanism by which nitric oxide modulates cancer cell growth and metastasis on cellular and molecular level is still not fully understood. This work utilized confocal microscopy and fluorescence microplate reader to investigate the effects of exogenous NO on the mobilization of calcium, which is one of the regulators of cell migration, in HeLa cells. The results show that NO elevates calcium in concentration‐dependent manner in HeLa cells. And the elevation of calcium induced by NO is due to calcium influx and calcium release from intracellular calcium stores. Moreover, calcium release from intracellular stores is dominant. Furthermore, calcium release from mitochondria is one of the modulation pathways of NO. These findings would contribute to recognizing the significance of NO in cancer cell proliferation and metastasis. SCANNING 36:258–262, 2014. © 2013 Wiley Periodicals, Inc.